2018
DOI: 10.1089/acm.2017.0153
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Combination of Melissa officinalis L. and Nepeta menthoides Boiss. & Buhse on Insomnia: A Triple-Blind, Randomized Placebo-Controlled Clinical Trial

Abstract: A combination of M. officinalis and N. menthoides Boiss. & Buhse could be an alternative sleep improvement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Another research group from Iran also discovered the combination of M. officinalis and Nepeta menthoides Boiss. & Buhse in sleep disorder [134]. A total of 102 patients participated in this study, but only 80 were selected after the screening.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research group from Iran also discovered the combination of M. officinalis and Nepeta menthoides Boiss. & Buhse in sleep disorder [134]. A total of 102 patients participated in this study, but only 80 were selected after the screening.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Selected patients have been treated with the dose of 1000 mg of M. officinalis plus 400 mg of N. menthoides or a placebo for four weeks. The 4-week trial demonstrated that a combination of both showed significant activity against insomnia (Trial registration number: IRCT2015040621592N2) [134].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…For centuries, MO has been used in traditional Chinese medicine (TCM), traditional Persian medicine (TPM), Ayurvedic medicine, Arabic medicine, and medieval European medicine for treating diverse health conditions, such as insomnia, migraines, neuroses, and hysteria, among others ( Shakeri et al, 2016 ). In the modern pharmacological studies, various human clinical trials ( Kennedy et al, 2002 ; Akhondzadeh et al, 2003 ; Kennedy et al, 2003 ; Kennedy et al, 2004 ; Kennedy et al, 2006 ; Cases et al, 2011 ; Alijaniha et al, 2015 ; Ranjbar et al, 2018a ; Ranjbar et al, 2018b ; Haybar et al, 2018 ; Heydari et al, 2018 ; Soltanpour et al, 2019 ; Araj-Khodaei et al, 2020 ; Noguchi-Shinohara et al, 2020 ; Shirazi et al, 2021 ), animal models ( Coleta et al, 2001 ; Guginski et al, 2009 ; Ibarra et al, 2010 ; Yoo et al, 2011 ; Taiwo et al, 2012 ; Feliú-Hemmelmann et al, 2013 ; Lin et al, 2015 ; Ghazizadeh et al, 2020 ; Talebi et al, 2022 ), and in vitro studies ( Kennedy et al, 2003 ; Awad et al, 2007 ; Awad et al, 2009 ; López et al, 2009 ; Sahin et al, 2016 ) have investigated the neurotherapeutic effects of MO extract, with most studies reporting its antidepressant, anti-stress, anxiolytic, anti-insomnia, and anti-oxidative stress (neuroprotective) properties. According to reported evidence, the neuropharmacological effects of MO extract are due to its various biological properties, i.e., its GABAergic properties (upregulation of γ-amino butyric acid (GABA) through GABA-transaminase (GABA-T) inhibition ( Awad et al, 2007 ; Awad et al, 2009 ; Yoo et al, 2011 ), GABA A receptor affinity ( Salah and Jäger, 2005 ; Abuhamdah et al, 2008 ; Sahin et al, 2016 )), modulation of the serotonergic pathway ( Dimpfel and Suter, 2008 ; Lin et al, 2015 ), and inhibition of acetylcholine esterase (AChE) ( Perry et al, 1996 ; Ferreira et al, 2006 ; Dastmalchi et al, 2009 ) and monoamine oxidase (MAO) enzymes ( Ulbricht et al, 2005 ; López et al, 2009 ; Taiwo ...…”
Section: Introductionmentioning
confidence: 99%
“…Another research group also discovered the combination of M. officinalis and Nepeta menthoides Boiss. & Buhse in sleep disorder [88]. The trial evaluated 80 patients treated with the 1000 mg dose of M. officinalis plus 400 mg of N. menthoides or a placebo for four weeks.…”
Section: Human Clinical Trialsmentioning
confidence: 99%